2009
DOI: 10.1167/iovs.08-2544
|View full text |Cite
|
Sign up to set email alerts
|

Rod and Rod-Driven Function in Achromatopsia and Blue Cone Monochromatism

Abstract: Purpose To evaluate rod photoreceptor and postreceptor retinal function in pediatric patients with achromatopsia (ACHR) and blue cone monochromatism (BCM) using contemporary electroretinographic (ERG) procedures. Methods Fifteen patients (age 1 to 20 years) with ACHR and six patients (age 4 to 22 years) with BCM were studied. ERG responses to full-field stimuli were obtained in scotopic and photopic conditions. Rod photoreceptor (Srod, Rrod) and rod-driven postreceptor (log σ, Vmax) response parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 80 publications
(75 reference statements)
5
32
0
1
Order By: Relevance
“…Less anticipated was the finding that a considerable percentage of patients had mild to moderate abnormalities of rod-mediated ERG, even though the genetic defect is cone specific. This has been previously reported in CNGA3 ACHM 10,37 and in other genetic forms of ACHM 38,39 and could reflect a reduced number of rods, dysfunction of rods, or abnormal connectivity of rods to postreceptoral neurons. 39,40 Our cross-sectional retinal imaging studies (based on a limited number of patients) showed no evidence of a reduced number of rod nuclei, but unexpectedly there was mild shortening of the ROS length within the central retina similar to recent findings in another Figure 5.…”
Section: Discussionsupporting
confidence: 74%
“…Less anticipated was the finding that a considerable percentage of patients had mild to moderate abnormalities of rod-mediated ERG, even though the genetic defect is cone specific. This has been previously reported in CNGA3 ACHM 10,37 and in other genetic forms of ACHM 38,39 and could reflect a reduced number of rods, dysfunction of rods, or abnormal connectivity of rods to postreceptoral neurons. 39,40 Our cross-sectional retinal imaging studies (based on a limited number of patients) showed no evidence of a reduced number of rod nuclei, but unexpectedly there was mild shortening of the ROS length within the central retina similar to recent findings in another Figure 5.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, we argue that there is no difference between the 15 Hz ERGs of an achromat and normal subjects for low flash strengths and that the primary and secondary rod pathways function normally. In the literature, the functioning of the rods in achromatic patients is generally described as normal [32][33][34][35][36], although recently, abnormalities in rod driven ERGs have also been reported [37,38]. Therefore, it would be interesting to measure 15 Hz ERGs in more patients with achromatopsia.…”
Section: Discussionmentioning
confidence: 99%
“…In few cases, a partial function loss has been reported, resulting in milder forms like incomplete ACHM, oligocone trichromacy, and cone dystrophy [25,26,27]. …”
Section: Genetic Background and Pathophysiologymentioning
confidence: 99%
“…Electroretinographic examinations typically show absent or markedly reduced cone responses, while rod responses are reported to remain normal or nearly normal [1,2,25]. However, deficits in rod and rod-mediated function have also been demonstrated by Moskowitz et al [26]. …”
Section: Clinical Manifestation and Diagnosticsmentioning
confidence: 99%